Search for CP violation using T-odd correlations in D+ → K+K0Sπ+π- and D+S → K+K0Sπ+π- decays - Lees, Jean-Pierre; Adametz, Aleksandra; Marks, Jörg; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2011)
We search for CP violation in a sample of 20 000 Cabibbo-suppressed decays, D+→K+K0Sπ+π−, and 30 000 Cabibbo-favored decays, D+s→K+K0Sπ+π−. We use 520 fb−1 of data recorded by the BABAR detector at the PEP-II asymmetric-energy e+e− collider operating at center of mass energies near 10.6 GeV. We search for CP violation in the difference between the T-odd asymmetries obtained using triple product correlations of the D+ (D+s) and D− (D−s) decays, respectively. The T violation parameter values obtained are AT(D+)=(−12.0±10.0stat±4.6syst)×10−3 and AT(D+s)=(−13.6±7.7stat±3.4syst)×10−3, which are consistent with the standard model expectations.